Factor Analysis for Predicting the Structural Reorganization of the Microvasculature of the Kidneys in Patients with Glomerulonephritis and Arterial Hypertension - E. S. Levitskaya; M. M. Batiushin; E. A. Sinel’nik; D. I. Zakusilov (Архивъ внутренней медицины)
Objectives. Evaluation of the relationship of clinical, laboratory and morphological factors with remodeling of small-diameter renal arteries in patients with glomerulonephritis (GN) and arterial hypertension (AH). Materials and methods. The study included 105 patients (average age 37.1±1.2 years) with primary GN and hypertension who had indications for morphological investigation of kidney tissue. All patients underwent a standard examination for kidney disease, a morphological study of kidney tissue with a description of the changes that occur in the presence of glomerulonephritis, corresponding to the individual severity of the pathological process. The presence of signs of a tubulointerstitial component of damage (or tubulointerstitial component — TIC) in the form of tubulointerstitial infl ammation (TIV), fi brosis (TIF) was assessed. Vasometry of the interlobular artery (IA) was performed. The value of the intima-media complex (IMC) was considered to be a sign of IA remodeling. A sign of MA remodeling was considered to be an intima-media complex (IMC) value of more than 30.43 μm. Results. Among clinical and laboratory risk factors, an increase in systolic blood pressure has a statistically signifi cant effect on the likelihood of increasing IMC (χ2-criterion = 5.76, p = 0.016), arterial hypertension stage (χ2-criterion = 9.45, p = 0.002), blood urea level (χ2-criterion = 8.11, p = 0.004), decrease in glomerular fi ltration rate (χ2-criterion = 5.0, p = 0.025), increase in the stage of chronic kidney disease (χ2-criterion = 10.32, p = 0.001). The presence of signs of GN progression, such as an increase in erythrocyte sedimentation rate (ESR) or proteinuria, did not have a statistically significant effect on the risk of IA remodeling (p>0.05). The increase in IA IMC is affected by the presence of hyalinosis of glomerular capillary loops (χ2-criterion = 7.56, p = 0.006), periglomerular hyalinosis (χ2-criterion = 6.96, p = 0.008), sclerosis of the glomerulus (χ2-criterion = 3.9, p = 0.048), increased fibrosis of tubulointerstitium (χ2-criterion = 12.16, p = 0.0005). Conclusion. In GN and AH, remodeling of small-diameter renal vessels occurs due to the influence of AH and its severity, tubulointerstitial changes in the renal tissue. New risk factors for vascular remodeling have been obtained — changes in the glomerulus. At the same time, the inflammatory and autoimmune mechanisms of GN were not associated with changes in the vascular wall. The role of hypertension is decisive in changing the structure of small-diameter kidneys.